Anti-inflammatory effect of biologic therapy in patients with psoriatic disease: A prospective cohort FDG PET study - Boczar, Kevin E.; Beanlands, Rob S.; Glassman, Steven J.; Wang, Jerry; Zeng, Wanzhen; deKemp, Robert A.; Ward, Natalie C.; Fehlmann, Christophe A.; Wells, George A.; Karsh, Jacob; Dwivedi, Girish (Journal of nuclear cardiology, 2023)
The aim of the study was to evaluate the changes in central vascular inflammation measured by FDG PET and myocardial blood flow reserve (MFR) determined by 82Rb PET following therapy with biologic agents for 6 months in patients with psoriatic arthritis (PsA) and/or cutaneous psoriasis (PsO) (group 1) and compare with PsO subjects receiving non-biologic therapy (group 2) and controls (group 3). Target-to-background ratio (TBR) by FDG PET in the most diseased segment of the ascending aorta (TBRmax) was measured to assess vascular inflammation. 82Rb PET studies were used to assess changes in left ventricular MFR. A total of 34 participants were enrolled in the study (11 in group 1, 13 in group 2, and 10 controls). A significant drop in the thoracic aorta uptake was observed in the biologic-treated group (ΔTBRmax: − .46 ± .55) compared to the PsO group treated with non-biologic therapy (ΔTBRmax: .23 ± .67). Those showing response to biologic agents maintained MFR compared to who showed no response. In a cohort of psoriasis patients treated with biologics, FDG uptake in the thoracic aorta decreased over the study period. Patients who demonstrated a significant anti-inflammatory response on FDG PET imaging maintained their MFR compared to non-responders.